Evaluation model of node importance in directed scale-free network based on cascade failure - Haoran LIU; Xingqi WANG; Yujing DENG; Yuhua QIN (Dianxin kexue)
In order to evaluate the importance of nodes in a directed scale-free network accurately,the protection strategy can be better implemented and the destruction resistance of the network can be improved.Considering the changes of node load and network connectivity before and after cascading failure,a directed scale-free network node importance evaluation model based on cascading failure was proposed.Firstly,a cascading failure model of directed network was established to deduce the load of nodes before failure.Then,a node importance evaluation model was constructed by combining the node load and its location during data transmission.Experimental results show that when the network is attacked selectively,the number of generated sub-graphs and the network robustness change more obviously after the failure of key nodes measured by the model,providing experimental data for specific applications.